High resolution 3-D angle of arrival determination for indoor UWB multipath propagation - Zhang, Y; Brown, A; Malik, W; Edwards, D (2008)
Propagation measurements using a large array are used to study the angle of arrival (AOA) across the ultrawideband (UWB) frequency range of 3.1 to 10.6 GHz. A two-dimensional Unitary ESPRIT algorithm is employed to give a high resolution estimation of AOA including both the azimuth and elevation angles of multipath components. The frequency dependence of AOA is investigated over the UWB frequency band. The multipath rays form clusters in both angular and temporal domains. Within a cluster the azimuth and elevation AOAs are determined to follow Laplacian and Gaussian distributions respectively. In the indoor environment considered, a typical cluster extends over an angular sector of approximately 14 degrees in azimuth and 9 degrees in elevation, with up to 5 clusters observed. We note that these propagation characteristics will allow UWB systems to utilise smart antennas or MIMO structures to improve overall throughput. © 2008 IEEE.